Applied mathematical and physical formulas : a quick reference for engineers, technicians, toolmakers, mechanists, students, and teachers - Boljanovic, Vukota (Industrial Press, Inc., 2015)
Annotation The new and revised version of this comprehensive pocket reference guide is ideal for anyone who deals with physics, chemistry, mathematics, finance, and computer systems and needs to review or quickly refresh their memory of what they studied in school. It covers the fundamentals of arithmetic, algebra, geometry, trigonometry, and analytical geometry, and statistics, and presents the application of differential equations and integral calculus. It reveals the comparative advantages of binomial distribution, standard distribution, Poisson distribution, and normal distribution, and includes most used definitions and formulas of kinematics, dynamics, statics, mechanics of fluids, thermal variable of state, thermodynamics, electricity and magnetism, light, and atomic and nuclear physics. It also presents applications and solutions to problems concerning simple interest, compound interest, effective rate, annuity, amortization of loans, and sinking fund payments.FeaturesA quick reference for engineers, technicians, toolmakers, machinists, students, and teachers.Includes more than 1,300 formulas, definitions, and figures used in mathematics and physics, plus complete coverage of S.I., metric, and U.S. customary units.New to this revised edition are sections on arithmetic, mathematical fundamentals of computer science, units of measure in precious metals, and more.Key topics have been clarified, and more than 150 line illustrations have been improved.The index has been expanded to help guide readers through this information-packed reference."
Keywords: Mathematics -- Formulae -- Handbooks, manuals, etc.; Physics -- Formulae -- Handbooks, manuals, etc.; elektronické knihy; electronic books